A RECONNAISSANCE OF MUAMALAH FIQH ON THE PROFIT-SHARING SYISTEM IN NUTMEG MANAGEMENT (CASE STUDY IN MEUKEK SUB-DISTRICT) - Nurdin, Ridwan; Yuhermansyah, Edi; Afrillia, Shintia (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2023)
Islam teaches to muamalah correctly in accordance with the shari'ah that is taught. There are several systems of mu'amalat cooperation known as muzara'ah, mukhabarah, ijarah, musaqah and syirkah. In the current economic system, the concept of profit sharing is widely used by the community with modifications that can be made freely by the parties in the business. Profit sharing is a cooperative relationship between two or more people in terms of capital, skills, or trust in a particular business with profit sharing based on a ratio. Meukek District is an area that still has a lot of nutmeg plants, although not as much as in the past. The owner of the nutmeg plantation handed over his garden to someone who was trusted to take care of his garden, because the garden owner did not have time to manage the garden. The handover of the garden was based on the results of deliberation between the two parties, which later the results from the garden were divided into two. The purpose of this study was to determine the profit-sharing system for nutmeg management in Meukek District. The research approach used by the author in the discussion of this thesis is a qualitative approach. Data collection techniques used are observation, interviews and documentation. The profit-sharing system for the management of nutmeg in the Meukek Sub-district The agreement is carried out only orally, not in writing by means of mutual consultation regarding the revenue-sharing system from the agreed management of nutmeg. The duration of the cooperation depends on the mutual agreement between the garden owner and the cultivator. The distribution of the results is done in the form of money instead of nutmeg, after the nutmeg is harvested, the tenant sells it first and then the money from the sale of the nutmeg is then distributed between the owner and the cultivator. If a loss occurs, it will be shared between the owner and the cultivator. The Fiqh Mu'amalah review of the profit-sharing system in the management of nutmeg in Meukek District has met the requirements and harmony in terms of distribution of results in accordance with the contract, implementation, and distribution results that do not harm one party and on the basis of mutual assistance in its implementation.